(E)-3-(3,5-Dimethoxyphenyl)-1-(2-methoxyphenyl)prop-2-en-1-one - Lim, Yoongho (International Union of Crystallography, 2013)
In the title molecule, C(18)H(18)O(4), the dihedral angle between the benzene rings is 52.52 (7)°. The C=C bond of the central enone group adopts a trans conformation. The relative conformation of the two double bonds in the enone group is s-transoid. In the crystal, molecules are linked by pairs of weak C—H⋯O hydrogen bonds, forming inversion dimers.